Differential Cross Section With Volkov-Thermal Wave Function in Coulomb Potential - Dhobi, S. H.; Gupta, S. P.; Yadav, K.; Nakarmi, J. J.; Jha, A. K. (National Research and Innovation Agency, 2024)
Laser-assisted thermal electron-hydrogen atom elastic scattering was studied in the first-born approximation. The initial and final states of the projectile electron are described by the modified Volkov wavefunctions known as Volkov-Thermal wavefunctions. The laser-assisted thermal electron with energy ranges from 0.511 MeV to 4 MeV was considered to study the differential cross section (DCS) at azimuthal angles 30° and 14.7°, and laser-assisted field photon energy 1 eV to 3 eV are very weak at room temperature is around the room temperature 280 K to 300 K. The destructive interference was observed when a thermal electron absorbed a single photon from the laser field but no interference was found when a thermal electron emitted an electron to the laser field at a scattering angle . The DCS with eT scattering was found to be greater than a nonthermal electron in presence of laser field with scattering angle and incidence energy of the electron.